2021
DOI: 10.1080/13880209.2021.1914114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dacomitinib on the pharmacokinetics of poziotinib in vivo and in vitro

Abstract: Context: Dacomitinib and poziotinib, irreversible ErbB family blockers, are often used for treatment of non-small cell lung cancer (NSCLC) in the clinic. Objective: This study investigates the effect of dacomitinib on the pharmacokinetics of poziotinib in rats. Materials and methods: Twelve Sprague-Dawley rats were randomly divided into two groups: the test group (20 mg/kg dacomitinib for 14 consecutive days) and the control group (equal amounts of vehicle). Each group was given an oral dose of 10 mg/kg poziot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The precision, accuracy and recovery of poziotinib in samples have been tested and verified in our previous study 9 A representative chromatogram of plasma sample at 1 h after oral administration of poziotinib in rats is shown in Figure 1 . Figure 2 shows the mean plasma concentration‐time curves of poziotinib in rats after single oral administration of 2 mg/kg poziotinib or pretreatment with Schisandrins.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…The precision, accuracy and recovery of poziotinib in samples have been tested and verified in our previous study 9 A representative chromatogram of plasma sample at 1 h after oral administration of poziotinib in rats is shown in Figure 1 . Figure 2 shows the mean plasma concentration‐time curves of poziotinib in rats after single oral administration of 2 mg/kg poziotinib or pretreatment with Schisandrins.…”
Section: Resultsmentioning
confidence: 61%
“…In liver microsomes incubation system, 10 poziotinib metabolites (M1‐M10) were measured, and dihydroxylation (M1) and demethylation (M2) were mainly metabolized by CYP3A4 and 2D6, respectively 7 . The chemical structures of poziotinib, M1 and M2 have been presented in a previous report 9 . Wang et al observed that poziotinib inhibited the enzymatic activity of CYP2B1 and 2C11 to varying levels without concentration‐dependence or time‐dependence via in vitro and in vivo experiments 8 .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Erlotinib, an epidermal growth factor receptor tyrosine kinase inhibitor, is used to treat some types of non-small cell lung cancer and advanced pancreatic cancer ( Carter et al, 2022 ). Vorinostat ( Lin et al, 2021 ), dacomitinib ( Ji et al, 2021 ), vandetanib ( Carvalho et al, 2022 ), afatinib ( Wu et al, 2021 ), and vismodegib ( Duplaine et al, 2021 ) also have anticancer effects in malignancies. In the future, further experiments are required to confirm their therapeutic potential for the targeted therapy of HCC.…”
Section: Discussionmentioning
confidence: 99%